THE FOREIGN POLICY IDEOLOGY OF AMERICAN NEOCONSERVATISM - Turaev, Abrar (Научно-просветительский журнал "Наставник", 2020)
This article discusses the neoconservative ideology of the United States in the field of foreign policy, the formation, development of ideas and concepts, and the role of modern US political discourse. It also analyzes the role of foreign policy in the evolution of neoconservatism, the foreign policy views of neoconservatism theorists and their conflicting character. Attention is paid to the peculiarities of the periodization of the evolution of the doctrine of foreign political neoconservatism.